The Extent of Awareness of Intermediate Stage Mathematics Teachers about Digital Educational Technologies in Jeddah, Saudi Arabia - Al-Thalabi, Rawiya Omar AbdulAziz; Al-Maliki, AbdulMalik Musfir Hassan (Journal of Educational and Psychological Sciences, 2021)
The research aimed to examine the extent to which Teachers of Mathematics at the intermediate stage in Jeddah, Saudi Arabia, were aware of digital educational technologies. It used the descriptive method, and a questionnaire of (25) items divided into three areas and the research sample consisted of (230) Intermediate School Mathematics teachers in Jeddah. The results indicated that the mathematics teachers ’awareness of digital educational technologies was of a medium agreement score, with an arithmetic mean of (3.08) and a percentage of (61.6%). The awareness of the cognitive dimension of technologies obtained a medium agreement score, with an arithmetic mean of (3.36), and a percentage of (67.2%). Also, the awareness of the skill dimension of technologies obtained a medium agreement score, with an arithmetic mean of (2.80), and a percentage of (55.9%). The results also showed that the teachers face obstacles in using digital educational technologies to a very large extent, with an arithmetic mean of (4.23), and a percentage of (84.5%). The results did not reveal any statistically significant differences in the degree of awareness of mathematics teachers to digital educational technologies and the obstacles to their use due to years of experience. The research recommended the necessity of enhancing the knowledge and skill aspects of modern educational technologies among intermediate school teachers in Jeddah, as well as overcome obstacles to their use of these technologies.
Keywords: Digital Technologies; Mathematics Teachers; Intermediate Stage